Kinematics Analysis and Workspace Solution for the Heterogeneous Double-drive Universal Joint - Li Zhongtao; Luo Tianhong (Jixie chuandong)
A heterogeneous double driving universal joint (HDD-UJ) is proposed, which can realize the pitching motion and the rolling motion. The HDD-UJ uses a universal joint as the prototype of the mechanism, with the motor as the main drive source and the electrostrictive material as the auxiliary drive source. Through the design of the HDD-UJ virtual prototype model, the integrated characteristics of the transmission integration are determined, and the transmission integration mechanism of the joint is described. The spatial motion coordinate system of the HDD-UJ is established, and its kinematics analysis is carried out and the kinematics equation is derived. Based on the mathematical principle of space geometry, the spatial motion range of the HDD-UJ is obtained, and the virtual simulation experiment of motion workspace is carried out. The simulation results show that the HDD-UJ structure is novel and simple, with high integration, and has two degrees of freedom. It can realize a wide range of space operations, and theoretical basis for the study of structural optimization and motion precision control strategies of subsequent joints is provided.